The growth of China’s internet technologies and digital economy - Д.Б., Дауен; Т., Қудайбергенов (Journal of Oriental Studies, 2020)
The article presents an analysis China’s digital economy’s development and the latest achievements of China in this area. The digital economy already covers 30.6% of China’s GDP. Without a doubt, the digital economy has become China’s busiest area of economic development in recent years. In 2017, it was first mentioned in a government report. They began to consider it as a new force that accelerated the growth and development of China’s economic life. The very first results of the development of China’s digital economy have shown the whole world the enormous potential and attractiveness of the irregular growth of science and technology. The digital economy is the modern development path of the global economy. It can not only increase economic productivity in undeveloped regions, but also, more importantly, give the people of these regions the most diverse opportunities for positive change. With digital communications, people from even the most remote areas can enjoy the same high-quality content as residents of large cities. The population of the undeveloped regions will be able to obtain the necessary information in the field of education, medicine, trade operations, etc., with a minimum cost, sell their agricultural products at higher prices. The digital economy provides opportunities to help the poorest. This is what inspires people in developing countries. Key words: mobile payments, cloud computing, network security, e-commerce.